The Deviance Information Criterion in Comparison of Normal Mixing Models. (22nd August 2014) - Fung, Thomas; Wang, Joanna J.J.; Seneta, Eugene
Summary Model selection from several non‐nested models by using the deviance information criterion within Bayesian inference Using Gibbs Sampling (BUGS) software needs to be treated with caution. This is particularly important if one can specify a model in various mixing representations, as for the normal variance‐mean mixing distribution occurring in financial contexts. We propose a procedure to compare goodness of fit of several non‐nested models, which uses BUGS software in part.